Technical Analysis of Organic Rankine Cycle System Using Low-Temperature Source to Generate Electricity in Ship - Akram Faisal; Taufik Fajar Nugroho (Jurnal Teknik ITS, 2016)
Nowadays, the shipping sector has growth rapidly as followed by the increasing of world population and the demands for public transportation via sea. This issue entails the large attention on emission, energy efficiency and fuel consumption on the ship. Waste Heat Recovery (WHR) is one of the solution to overcome the mentioned issue and one of the WHR method is by installing Organic Rankine Cycle (ORC) system in ship. ORC demonstrate to recover and exploit the low temperature waste heat rejected by the ship power generation plant. The main source of heat to be utilized is obtained from container ship (7900 kW BHP, DWT 10969 mt) ship jacket water cooling system and use R-134a as a refrigerant. The main equipment consists of evaporator, condenser, pump and steam turbine to generate the electricity. The main objective is to quantifying the estimation of electrical power which can be generated at typical loads of the main engine. As the final result of analysis, the ORC system is able to generate the electricity power ranged from 77,5% - 100% of main engine load producing power averagely 57,69 kW.